Research on Operational Process Optimization Strategy during Cloud Service Migration - Li, Fangyuan (Journal of Computer, Signal, and System Research, 2025)
The cloud service migration of enterprises has begun to rely on digital transformation, but in the process of transformation, there may be problems such as disorganization of operational processes, slow response and poor coordination of systems. This paper mainly discusses how artificial intelligence can be applied to process identification, decision analysis, resource allocation and system coordination, and further describes the importance of virtualization technology, data synchronization mechanism and automatic arrangement strategy, proposes to take intelligence as the main line to improve migration rate and intelligent operation, and gives suggestions for enterprises to achieve effective and stable cloud operation architecture.